Pro SQL Server 2005 - Rizzo, Thomas (Apress, 2011)
SQL Server 2005 is next generation of SQL Server database and represents a massive leap forward for SQL Server developers in terms of programming options, productivity, database management and analysis. This book will take a deep look at the full range of SQL Server enhancements that will give meaningful and relevant examples that show not just how these new features work, but also how to architect their applications in order to exploit the new features most effectively.